SlCNGC1 and SlCNGC14 Suppress Xanthomonas oryzae pv. oryzicola-Induced Hypersensitive Response and Non-host Resistance in Tomato - Zhang, Xuan-Rui; Xu, You-Ping; Cai, Xin-Zhong (Frontiers in Plant Science, 2018)
Mechanisms underlying plant non-host resistance to Xanthomonas oryzae pv. oryzicola (Xoc), the pathogen causing rice leaf streak disease, are largely unknown. Cyclic nucleotide-gated ion channels (CNGCs) are calcium-permeable channels that are involved in various biological processes including plant resistance. In this study, functions of two tomato CNGC genes SlCNGC1 and SlCNGC14 in non-host resistance to Xoc were analyzed. Silencing of SlCNGC1 and SlCNGC14 in tomato significantly enhanced Xoc-induced hypersensitive response (HR) and non-host resistance, demonstrating that both SlCNGC1 and SlCNGC14 negatively regulate non-host resistance related HR and non-host resistance to Xoc in tomato. Silencing of SlCNGC1 and SlCNGC14 strikingly increased Xoc-induced callose deposition and strongly promoted both Xoc-induced and flg22-elicited H2O2, indicating that these two SlCNGCs repress callose deposition and ROS accumulation to attenuate non-host resistance and PAMP-triggered immunity (PTI). Importantly, silencing of SlCNGC1 and SlCNGC14 apparently compromised cytosolic Ca2+ accumulation, implying that SlCNGC1 and SlCNGC14 function as Ca2+ channels and negatively regulate non-host resistance and PTI-related responses through modulating cytosolic Ca2+ accumulation. SlCNGC14 seemed to play a stronger regulatory role in the non-host resistance and PTI compared to SlCNGC1. Our results reveal the contribution of CNGCs and probably also Ca2+ signaling pathway to non-host resistance and PTI.